Biodiversity and phylogeny of Marasmius (Agaricales, Basidiomycota) from Madagascar - Shay, Jackie E.; Desjardin, Dennis E.; Perry, Brian A.; Grace, Chris L.; Newman, Danny S. (Phytotaxa, 2017)
Prior to this monographic treatment, limited research on the genus Marasmius (Basidiomycota, Agaricales) had been conducted in Madagascar. Based on field work in January 2013 and January–February 2014, which generated 45 specimens of Marasmius sensu stricto, supplemented by herbarium exsiccatae and published literature, 35 species of Marasmius are documented from Madagascar. Of these, 5 species are recognized herein as new to science, viz., Marasmius madagascariensis, M. rubrobrunneus, M. dendrosetosus, M. sokola and M. tanaensis; an additional 11 species represent new distribution records for Madagascar. Species delimitations are based on comprehensive morphological descriptions and molecular sequences (ITS) data. Line drawings of salient micromorphological features, color photographs of basidiomes, comparisons with allied taxa, a key to aid in identification, and phylogenetic inferences are provided.